Improving Students’ Speaking Ability through Constructivisme Approach by Using Class Presentation at Seventh Grade Students of MTs Negeri 1 Kota Serang - Astry Wulandari (UICELL, 2020)
English for Foreign Language is one of the most major part in education. As a part of English skill, speaking is one of the crucial thing as a communication. But infact, it should be learnt earlier even in junior high school. There are some problems come up when students take this skill, the lack of time to learn English and the number of students are the biggest problem and it needs to solve. Besides, teacher sometime still use a convention method, so to improve students’ ability in speaking, teacher should have a goood way to teach. Class presentation is one of the solution to enhance students’ speaking skill. They have a time to speak up in turn and by constructivisme approach, students have a change to learn EFL regularly. This research uses action research where contains two cycles as comparission the result. Meanwhile this research uses random sampling to consider the partisipation and it takes place at seventh grade junior high school of MTs Negeri 1 Kota Serang. to get the result of data, this reseacrh uses triangulation data that consist of three parts, they are, observation, interview, test and document. This research is started from identifying problem, problem formulation, acting, collecting data and publishing.